Collective Efficacy and Social Cohesion in Miami-Dade County, Florida, 2010-2011 - Varano, Sean ([Verlag nicht ermittelbar], 2016)
These data are part of NACJD's Fast Track Release and are distributed as they there received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except of the removal of direct identifiers. Users should refer to the accompany readme file for a brief description of the files available with this collections and consult the investigator(s) if further information is needed.The current study sought to expand the current understanding of the psychometric characteristics of the collective efficacy scale at the individual level and the role of collective efficacy in promoting safe, healthy community conditions. A team of interviewers consisting of residents of the targeted neighborhoods were selected and trained to administer the field surveys (NIJ Neighborhoods Resident Survey Data, 108 variables, n=649). In order to ensure accuracy of the responses, the field supervisor conducted telephone validation for approximately ten to fifteen percent of the surveys. In addition to resident surveys, trained research staff conducted systematic social observations (SSOs) of street segments in selected neighborhoods noting physical and social indictors.